2019
DOI: 10.1026/0012-1924/a000222
|View full text |Cite
|
Sign up to set email alerts
|

Entwicklung und Validierung eines Fragebogens zur Erfassung von Freude am Schulsport im Jugendalter (FEFS-J)

Abstract: Zusammenfassung. Die vorliegende Studie dient der Entwicklung und Validierung eines Messinstruments zur differenzierten Erfassung von Freude am Schulsport im Jugendalter. Basierend auf theoretischen Ansätzen wird das Konstrukt Sport-Enjoyment ( Scanlan & Simons, 1992 ) im Rahmen eines 3-Faktorenmodells (Vergnügen; Flow-Erleben; Erholung) weiterentwickelt. Die psychometrische Überprüfung erfolgt anhand einer Gesamtstichprobe von N = 1 253 Schülerinnen und Schülern der Klassenstufen 7 – 10. Die postulierte 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…Therefore, the specific games used in this study may work better with younger students than with older students. Previous research showed that younger students experience more enjoyment than older students anyway [39]. Hence, future studies should look more detailed at the reasons for these differences and may investigate separately the length of the intervention program and different class levels.…”
Section: Limitations and Directions Of Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the specific games used in this study may work better with younger students than with older students. Previous research showed that younger students experience more enjoyment than older students anyway [39]. Hence, future studies should look more detailed at the reasons for these differences and may investigate separately the length of the intervention program and different class levels.…”
Section: Limitations and Directions Of Future Researchmentioning
confidence: 99%
“…For more information about the sample distribution, see Table 1. [39,40]). Pleasure is related to the affective experience in physical education (e.g., "Physical education is fun").…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The three scales of the QUAEPE comprise three items each, answered on a four-point rating scale, ranging from 0 (never) to 3 (always). 1 Engels and Freund (2019) found empirical support for the assumed three-factor structure.…”
mentioning
confidence: 87%
“…The pleasant feeling experienced after conduct of physical activity can also be understood as a feeling of recovery. Engels and Freund (2019) consider pleasure as an anticipated antecedent of physical education, flow as a positive feeling during physical education, and recovery as a desirable consequence of physical education. The three scales of the QUAEPE comprise three items each, answered on a four-point rating scale, ranging from 0 (never) to 3 (always).…”
mentioning
confidence: 99%